Flood Photography and the Visual Component of Environmental American Studies - Sam Hawksford White (New Area Studies)
This article develops a new approach for using photographic sources that might be of interest to American Studies scholars whose research contributes broadly to environmental education. Over the past forty years of photographic scholarship, scientific and other record images have become relatively prominent as primary sources. This visual material can be used to interrogate past responses to flooding and other environmental events. On the other hand, discourses around social documentary continue to frame how the human impacts of rapidly changing environments are visualised. By comparing two sets of images from the 1930s, the article juxtaposes the approaches of photographers associated with these two conventionally distinct areas to offer a more rounded view of flood photography. The discussion starts with a reflective section detailing how I arrived at my current research project. Following this, the categories of scientific and social documentary photography are described relationally in the context of the agencies of the New Deal, in the process setting out an argument for the contribution that engaged visuality can make to Environmental American Studies. Afterwards, the attention shifts to focus on images from two official contexts. The first example concerns record photography from the Soil Conservation Experiment Station in Bethany, Missouri, whilst the second considers photographs that the Resettlement Administration produced in response to flooding in Posey County, Indiana, in 1937. The article concludes by remarking on some of the implications of this method for how American Studies researchers currently conduct environmentally focused projects.